THE RELATIONSHIPS HOW TO LEARN WITH STUDENT LEARNING OUTCOMES IN THE STEEL STRUCTURE COURSE DEPARTMENT OF BUILDING ENGINEERING STUDY PROGRAM IN CIVIL ENGINEERING FACULTY OF ENGINEERING -PADANG STATE UNIVERSITY - 1797-1816 , Gusnaldi (CIVED, 2016)
This research is motivated by the problem of the low value of the students in the subject of steel structures Building Engineering Education Program in the Department of Civil Engineering. Due to lack of effective and efficient learning students during class. This study aims to reveal the relationship between learning the learning outcomes of students in the course of steel structures in the Department of Civil Engineering Faculty of Engineering, Padang State University. This type of research is the study korelational. The population in this study is the 2014 generation students who have taken courses steel structures enrolled in semester July-December, 2015 as many as 64  samples in this study 56 people were taken by proportional random sampling. The data used are primary data and secondary data. Primary data were obtained from the questionnaire to the students on how to learn, while secondary data is student results. Data analysis technique used is descriptive analysis, correlation analysis and analysis of significance. The analysis showed that there is a significant relationship and very significant between learning the learning outcomes of students in the course of steel structures in the Department of Civil Engineering FT-UNP. Significant level of 5% with 95% confidence level. It can be seen from the r arithmatic > r table. Based on the acquisition of these test results can be concluded that there is a significant relationship and very significant between learning the learning outcomes of students in the course of steel structures in the Department of Civil Engineering FT-UNP. Keywords: How To Learn, Learning Outcomes, Steel Structure